Some physical properties of gelatin films in relation to hard capsule production - Melia, Colin David (1983)
Hard gelatin capsules are manufactured from blends of limed ossein (LOG), acid ossein and acid pigskin gelatins, with LOGS usually forming the main portion of the blend. Unfortunately, the quality of the finished capsule cannot be predicted by routine quality control tests and 'poor' batches of LOG are encountered which form unsatisfactory capsules. In addition, differences between gelatin types are encountered in practice but the supporting literature is sparse and conflicting.